MSME Education Level, Not a Driver of Acceleration Halal Certification Program - Syarofi, Muhammad; Nur Syam; Muhammad Lathoif Ghozali, (International Journal of Scientific Research and Management (IJSRM), 2024)
The implication of UUJPH No. 33 of 2014 is that products that enter, circulate and are traded in the territory of Indonesia must be halal certified, however, the UUJPH is running slowly due to the low level of education of MSMEs and the low interest of MSMEs to have halal certificates, and there is no Banyuwangi Regent Regulation to strengthen the UUJPH. The purpose of this study was to determine that the level of education as a driver of the acceleration of the halal certification program. This research method uses a qualitative approach with a case study type of research, the research informants are the Banyuwangi halal task force, P3H, and business actors, data analysis using the Miles and Huberman Interactive model. The results showed that the level of education is not a driving force for the acceleration of the halal certification program in Banyuwangi MSMEs, because the education level of each MSME is not a strong basis for registering halal certificates, just as MSME academic degrees are not the main factor in creating quality products. This research rejects Soerjono's theory that the higher a person's education will make him tend to be in the degree of legal compliance and legal awareness. It can be formulated that the form of UMKM legal compliance with the UUJPH regarding halal certification obligations will be obeyed if there is education, socialization and assistance from the Halal Product Process Assistance not based on their level of education.